LEARNING SPEAKING THROUGH COMMUNICATIVE GRAMMAR ON SYSTEMATIC FUNCTIONAL LINGUISTICS (SFL) - edy suseno (ELT Worldwide: Journal of English Language Teaching, 2020)
Practicing speaking is very important for students to exchange ideas with others. Although having learned English for the years, many EFL students face problems in delivering the ideas orally. To overcome this kind of problem, an expo de facto research was conducted by observing the students’ scores in two subjects grammar and speaking. The students were in the first semester of the English education major. The research is to find out the material used in teaching grammar to develop speaking learning. To satisfy the aim of this study, the mixed-method was implemented. The data was analyzed qualitatively and confirmed quantitatively by the applying t-test.  From the analysis could be drawn that Using translation-method, podcast, noticing, and conversation in applying the communicative-grammar method enhances the students’ competence in speaking. It is very helpful for the teachers and students to implement it in learning grammar and speaking. It also provides the idea to other researchers to dig some deeper innovation in the same field.